Predicting and Exploring the Mechanisms of Erzhi Pill in Prevention and Treatment of Osteoporosis Based on Network Pharmacology and Zebrafish Experiments - Zhong Z; Li Y; Chen Y; Chen W; Li S; Lv X; Luo S (Dove Medical Press, 2021)
Zhiguo Zhong,1 Yuyun Li,2,3 Yan Chen,2,3 Wen Chen,2 Siyan Li,4 Xiaohua Lv,2 Shiying Luo2 1Traditional Chinese Medicine Department, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524023, People’s Republic of China; 2Department of Pharmacology, School of Pharmacy, Guangdong Key Laboratory for Research and Development of Natural Drugs, Marine Biomedical Research Institute, Guangdong Medical University, Zhanjiang, 524023, People’s Republic of China; 3Institute of Traditional Chinese Medicine and New Pharmacy Development, Guangdong Medical University, Dongguan, 523808, People’s Republic of China; 4School of Basic Medical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People’s Republic of ChinaCorrespondence: Shiying LuoDepartment of Pharmacology, School of Pharmacy, Guangdong Key Laboratory for Research and Development of Natural Drugs, Marine Biomedical Research Institute, Guangdong Medical University, No. 2 East Wenming Road, Xiashan District, Zhanjiang, 524023, Guangdong, People’s Republic of ChinaTel +86 13763058766Fax +86 7592388588Email luosy76@gdmu.edu.cnBackground: Erzhi Pill (EZP), a traditional Chinese medicine (TCM) prescription, has been widely applied to improve bone metabolism and treat osteoporosis (OP) in China. However, its effective constituents and mechanisms remain unclear.Methods: By combining network pharmacology and zebrafish experiments, an integrative method was employed to address this problem. Firstly, the disease targets of OP were collected from two public gene databases. Secondly, the active compounds and drug targets of EZP were obtained from the traditional Chinese medicine systems pharmacology database and analysis platform (TCMSP). Thirdly, a drug-target-disease interaction network was constructed, and the key active components were identified by analyzing the topological characteristics of the network. Finally, these predicted results were tested by zebrafish experiments and compared with those from the literature. Specifically, quercetin as an important representative active component of EZP was applied to wild type and transgenic zebrafish larvae to assess its effects on skull mineralization and osteoplastic differentiation.Results: Our study identified 72 active compounds, 220 targets and 166 signaling pathways probably involved in the prevention and treatment of OP by EZP, wherein quercetin, apigenin, daidzein, luteolin, ursolic acid and kaempferol could be the key compounds, while PI3K-Akt signaling pathway, TNF signaling pathway and IL-17 signaling pathway could be the key signaling pathways. The experiments indicated that quercetin attenuated both the decrease of skull mineralization and the inhibition of skull osteoplastic differentiation in zebrafish larvae trigged by dexamethasone.Conclusion: Our study not only investigated potentially effective constituents and mechanisms of EZP in the prevention and treatment of OP, but also provided a reference for the in-depth research, development and application of TCM.Keywords: Erzhi Pill, osteoporosis, network pharmacology, mechanisms, zebrafish, quercetin